2005
DOI: 10.3322/canjclin.55.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Difficult Communication Tasks in Oncology

Abstract: Effective communication skills enable physicians to improve patients' understanding of their illnesses, improve patient adherence to treatment regimens, use time efficiently, avoid burnout, and increase professional fulfillment. Common communication pitfalls include blocking, lecturing, depending on a routine, collusion, and premature reassurance. Cancer J Clin 2005;55:164 -177.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
377
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(399 citation statements)
references
References 57 publications
9
377
0
13
Order By: Relevance
“…The nurses need to communicate appropriately and give clear information to the patient, however, the nurses in our study emphasized that unless the patients are also communicating with the nurses, the level of effectiveness of the communication will be hindered due to the lack of trust and strength of the relationship between the two. Back et al (2005) reported that build trust is one of the aspect in communication that most valued by patients. Thus, communication among the nurses in our study is as much about building relationships, and creating safe space for the unique relationship between nurse and patient to grow, and then it is about merely transferring information about cancer and cancer care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurses need to communicate appropriately and give clear information to the patient, however, the nurses in our study emphasized that unless the patients are also communicating with the nurses, the level of effectiveness of the communication will be hindered due to the lack of trust and strength of the relationship between the two. Back et al (2005) reported that build trust is one of the aspect in communication that most valued by patients. Thus, communication among the nurses in our study is as much about building relationships, and creating safe space for the unique relationship between nurse and patient to grow, and then it is about merely transferring information about cancer and cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization estimates that without intervention 84 million people will die of cancer between 2005and 2015(WHO, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the disclosure timing is important to consider, as are general precautions and best practices surrounding disclosure of all bad news. [37][38][39] Given the unexpected nature of these revelations, the physician should take into account that this information is not only a surprise but also likely represents emotionally volatile information that could include life-threatening or life-altering information. 34,37 Research shows that disclosure timing affects how revealed information is understood, particularly in unexpected situations.…”
Section: Timing Of the Mistake Disclosurementioning
confidence: 99%
“…As suggested by Back et al, soliciting patient preference prior to a discussion is important. 9 These authors recommended using an approach called "ask-tell-ask." This approach emphasizes the importance of asking questions to assess a patient's needs, telling the patient the information that meets those needs, and asking again to assess the patient's understanding.…”
Section: Family/patient Perspectivementioning
confidence: 99%
“…A useful mnemonic highlighting the components of the empathetic response is NURSE: naming, understanding, respect, supporting, and exploring. 9 Using this technique, the provider starts by naming the emotion (anger, fear, disbelief); confirms a clear understanding of the patient's feelings; expresses respect verbally or nonverbally, letting the patient know the emotion is important; uses supporting statements that may express concern, reiterate understanding, or indicate a willingness to help; and closes by exploring additional concerns.…”
Section: Importance Of Empathymentioning
confidence: 99%